The Yellow Book Learning Methodology at Islamic Boarding Schools - Arrohmatan, Arrohmatan; Warisno, Andi; Ansori, Afif; Andari, An An; Nelson, Nelson (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to determine the yellow book learning method from the point of view of management science, including planning, organizing, implementing, and evaluating. This research uses the literature study method, in which researchers try to find data from various sources such as books, journals, and other research to compile, manage and present it to become information. Data collection techniques are carried out with documentation. Meanwhile, data analysis uses content analysis. The results showed that institutions applied five methods in teaching the yellow book at Islamic boarding schools, including sorogan, wetonan/bandongan, deliberation/ bahtsul Masa'il, market, Muhafadzoh, demonstrations, and classics. Islamic boarding schools and Madrasah Diniyyah generally implement institutions for learning the yellow book, a characteristic that cannot be separated from this learning is the large role of the Kiai (Teacher) and Santri (Students). Learning management that is applied other than the classical method needs to be carried out in writing and neatly. In contrast, the classical method is written and compiled in the bookkeeping of the Madrasah Diniyyah curriculum in Islamic boarding schools and Madrasah Diniyyah, which are independent outside Islamic schools. Thus the methodology of learning the yellow book in Islamic boarding schools is still conventional.